350 Examining the relationships among abrocitinib treatment, itch, skin pain and work and activity impairments in patients with atopic dermatitis: a mediation modelling analysis. (25th January 2023) - Silverberg, Jonathan I; Ständer, Sonja; Thyssen, Jacob P; Kim, Brian S; Castro, Carla; Bewley, Anthony; Misery, Laurent; Bushmakin, Andrew G; Cappelleri, Joseph C; Guler, Erman; Alderfer, Justine; Watkins, Melisa; et al.
Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disorder characterized by intense itch, skin pain and impaired quality of life. Skin pain is a common and bothersome symptom of AD and increases in prevalence and intensity with worsening disease severity. Abrocitinib is an oral, once-daily, selective Janus kinase-1 inhibitor approved for the treatment of moderate-to-severe AD. Abrocitinib treatment resulted in improvements in skin clearance as well as rapid itch reduction in patients with moderate-to-severe AD across multiple phase 3 studies. Work productivity loss and activity impairment were assessed in the phase 3 JADE MONO-2 (NCT03575871) trial, with greater improvements being associated with abrocitinib treatment compared with placebo. The mechanism(s) through which abrocitinib reduces work productivity loss and activity impairment are unclear. To describe the interrelationships among abrocitinib treatment, itch, skin pain, and work productivity and activity impairment using a mediation modelling analysis in patients with AD. Data from adult patients treated with abrocitinib monotherapy (200 or 100 mg) or placebo in JADE MONO-2 were included in this analysis. As separate outcomes, work productivity loss and activity impairment (outcome variables) were measured by the Work Productivity and Activity Impairment Questionnaire: Atopic Dermatitis version 2.0 (WPAI-AD 2.0). Itch and skin pain (mediator variables) were evaluated using the Pruritus and Symptoms Assessment for Atopic Dermatitis (PSAAD) item #1 ( How itchy was your skin over the past 24 h? ) and item #2 ( How painful was your skin over the past 24 h? ), respectively. Mediation modelling was conducted independently for work productivity loss and activity impairment. All available data at week 12 were used in the modelling. Effects with P < 0.05 were considered statistically significant. The direct effects of abrocitinib were estimated to be 7.3% ( P = 0.779) and 17.5% ( P = 0.258) on work productivity loss and activity impairment, respectively. The indirect effects of abrocitinib treatment on work productivity loss and, separately, on activity impairment mediated via itch were estimated to be 50.6% ( P = 0.017) and 20.9% ( P = 0.062), respectively, and via skin, pain were estimated to be 42.1% and 61.5%, respectively, ( P < 0.05 for both). The indirect effect of abrocitinib treatment on work productivity loss is mediated approximately equally through the reduction in itch severity and skin pain. The effect of abrocitinib treatment on activity impairment is mostly mediated indirectly through the reduction of skin pain, along with a smaller indirect contribution from the reduction in itch. These findings support further research into the extent that patients consider itch and skin pain as separate concepts in terms of their impact on work productivity.